THE INFLUENCE OF L1 ON L2 IN TRANSLATION: ERRORS MADE BY YOGYAKARTA STATE UNIVERSITY STUDENTS - Laser Romios (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2020)
This study investigates the errors made by Indonesian English learners within crosslinguistic interference between L1 and L2 (Indonesian and English). The data were gathered by making the respondents translate 6 Indonesian sentences which are commonly used during class presentation into proper English. Such task was aimed at investigating the interlingual preposition errors induced by the process of transfer between the target language (English) and the source language (Indonesian). The translation task was assigned in 22 October 2018 to 19 adult EFL learners of English Education Magister’s Program of Yogyakarta State University semester I. They were asked to translate the sentences from Indonesian into English within the allocated time. The task was conducted directtly by writing down the translation on a piece of paper. The data was then analyzed through Coder’s error analysis theory. The findings suggested that these particular English foreign language learners made the fewest errors on preposition omission – and more errors on wrong use and redundancy of prepositions.